First-episode olfactory hallucination in a patient with anxiety disorder: A case report - Jiang, Xingmei; Yuan, Yiwen; Li, Zhixiong; Ou, Ying; Li, Zhe (Frontiers in Psychiatry, 2022)
Abstract BACKGROUND Olfactory hallucination refers to olfactory perception in the absence of chemical stimuli. Although it has been associated with many neurological and psychotic disorders, it has rarely been reported as the first and only symptom in patients with anxiety disorder, and its treatment remains inadequate. CASE SUMMARY A 66-year-old woman who had been experiencing gradually worsening olfactory hallucinations for almost four years was diagnosed with generalized anxiety disorder. Olfactory hallucination disappeared after treatment with anti-anxiety drugs. CONCLUSION Olfactory hallucination can be the first and only symptom in patients with anxiety disorder and may be effectively treated with anti-anxiety medication. In fact, it can precede the diagnosis of anxiety disorder by several years.